Assessment of carvacrol-antibiotic combinations’ antimicrobial activity against methicillin-resistant Staphylococcus aureus - Al-Tawalbeh, Deniz; Alkhawaldeh, Yazan; M. Sawan, Hana; Al-Mamoori, Farah; Al-Samydai, Ali; Mayyas, Amal (Frontiers in Microbiology, 2024)
Introduction: This study aimed to assess the antimicrobial activity of carvacrol in combination with approved antibiotics against methicillin-resistant Staphylococcus aureus (MRSA).Carvacrol, a phenolic monoterpenoid component of essential oils, has demonstrated antimicrobial properties against gram positive and gram negative bacteria. The study evaluated the antimicrobial effects of carvacrol combined with sulfamethoxazole, linezolid, minocycline, and trimethoprim. Methods: The MRSA strain (ATCC-33591) was used, and various assays, including MIC determination, checkerboard assay, and microdilution assay were conducted.Results: The results showed that the combination of carvacrol with antibiotics yielded better outcomes compared to monotherapy, leading to reduced bacterial colonization. Carvacrol, sulfamethoxazole, and trimethoprim exhibited weak anti-staphylococcal effects, while linezolid and minocycline demonstrated stronger effects. This suggests that conventional antibiotic therapy may not be sufficient to effectively treat MRSA infections, potentially causing delays in healing or an exacerbation of the condition. Carvacrol combinations with two antibiotics displayed superior results compared to other pairs, indicating synergistic or additive effects of carvacrol with linezolid, minocycline, and sulfamethoxazole. Conclusion: These findings propose a new approach for developing drug molecules for MRSA treatment which combine volatile oils with available regimens. Further studies are recommended to evaluate the efficacy and biosafety of these combinations using in vivo or ex vivo models, aiming to minimize side effects and facilitate human trials. This study provides valuable insights into the potential use of carvacrol-antibiotic combinations as a novel therapeutic approach against MRSA.